Study on the pollution characteristics and emission factors of PCDD/Fs from disperse dye production in China. (August 2019) - Zhou, Xin; Zhou, Yanxiao; Liu, Jinsong; Song, Shuang; Sun, Junjun; Zhu, Guohua; Gong, Hongping; Wang, Ling; Wu, Chenwang; Li, Mufei
Abstract: According to an analysis of the input and output of polychlorinated dibenzo- p -dioxin and dibenzofurans (PCDD/Fs) of two disperse dye manufacturers, the average PCDD/F emission factor was 56.3 μg I-TEQ/T product, and dioxin was mainly emitted with products and solid waste. The PCDD/F concentrations of different series of disperse dyes varied from 2.87 to 323 pg I-TEQ/g, and the dominant congener was OCDD or 2, 3, 7, 8-TCDF with the highest ratio of 83.4% or 79.3%, respectively. The distributions of PCDD/F congeners in raw materials and the products were different, indicating that the structure of PCDD/Fs greatly changed in the synthesis process. PCDD/Fs in the wastewater and sludge of the companies are mainly from the production process of a product with dominant emission factors. Our results confirm that disperse dyes may be a source of PCDD/Fs, resulting in human exposure and environmental contamination. Highlights: The average PCDD/F emission factor is 56.3 μg I-TEQ/T product. The predominant emission of PCDD/Fs is with products and solid waste. OCDD or 2, 3, 7, 8-TCDF is the predominant congener in the disperse dyes. The structure of PCDD/Fs may change in the disperse dye synthesis process. Disperse dyes may be a source of PCDD/F human exposure and environmental contamination.